2012
DOI: 10.1016/j.brainres.2012.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone repression of astrocyte activation: Relevance to multiple sclerosis

Abstract: Mitoxantrone has been approved by the FDA for the treatment of multiple sclerosis (MS). However, the mechanisms by which mitoxantrone modulates MS are largely unknown. Activated astrocytes produce nitric oxide (NO), TNF-α, and IL-1β, molecules which can be toxic to central nervous system (CNS) cells including oligodendrocytes, thus potentially contributing to the pathology associated with MS. MCP-1 is a chemokine believed to modulate the migration of monocytes to inflammatory lesions present in the CNS of MS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Moreover, p28 can form a complex with cytokine‐like factor 1 (CLF‐1) (Crabe et al, ); human macrophages under inflammatory conditions have been shown to express CLF‐1 (Kass et al, ). Although human astrocytes can produce the IL‐12p40 subunit (Burns et al, ; Constantinescu et al, ), whether they can also express p35 is not resolved and no data is available pertaining to CLF‐1 production by astrocytes. Therefore, it remains possible that p28 or EBI3, especially in myeloid cells, combines with other partners.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p28 can form a complex with cytokine‐like factor 1 (CLF‐1) (Crabe et al, ); human macrophages under inflammatory conditions have been shown to express CLF‐1 (Kass et al, ). Although human astrocytes can produce the IL‐12p40 subunit (Burns et al, ; Constantinescu et al, ), whether they can also express p35 is not resolved and no data is available pertaining to CLF‐1 production by astrocytes. Therefore, it remains possible that p28 or EBI3, especially in myeloid cells, combines with other partners.…”
Section: Discussionmentioning
confidence: 99%
“…In these lines, therapeutic concepts such as the blockade of S1P receptors by FTY720 (34), inhibition of COX2 signaling by analogues of celecoxib (35), increase of cytosolic cGMP by sildenafil (36), as well as other immunomodulatory drugs like resveratrol (37), mitoxantron (38) and dimethylumarate (39) have been demonstrated to inhibit IL-1β production in astrocytes during EAE, the cuprizone induced model of demyelination in vivo as well as LPS induced astrocyte activation in vitro .…”
Section: Role Of Selected Pro- and Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Some drugs that are approved for therapy of MS, as well as some of those which have shown beneficial effects in clinical or preclinical trials, are known to affect NF-jB-regulated expression and iNOS activity, which may represent an important component of their mechanisms of action. Mitoxantrone (DNA-reactive agent), which is used for the treatment of patients suffering from SPMS, PRMS, or RRMS worsening, is known to suppress NF-jB DNA-binding activity and NO production in stimulated astrocytes (64). Teriflunomide (the inhibitor of pyrimidine de novo synthesis), which is used for oral treatment of patients suffering from RRMS (211), inhibits iNOS in astrocytes (316).…”
Section: The Inhibition Of Nf-kb and Inosmentioning
confidence: 99%